Reflection and Promotion of Pedagogical Practice in the Chilean Rural and Urban Classroom; [Reflexión y Promoción de la Práctica Pedagógica en el Aula Rural y Urbana Chilena] - Villalta-Paucar, M (Universidad Nacional Autonoma de Mexico, 2025)
The aim of the article is to analyze the process of reflection on pedagogical practice classroom interaction of female teachers in different sociocultural contexts. A mixed methodology was used in nine female elementary school teachers from urban and rural schools in Chile, who participated in a program Accompanying the Reflection of the Practice (ARP) to enhance the types of verbal exchanges and mediated learning experience theory (MLE) mediation criteria in the classroom. The teachers self-filmedtheir classes, reportedon the experience, and participated in researchinterviews. It was foundthat the MLE exchanges andcriteria changed significantly between pre- and post-ARP, with differences between urban and rural classrooms; reflection moved from the simple to the more complex level. In conclusion, reflection is associated with improving the levels of elaboration of the experience in the classroom by promoting exchanges with MLE criteria. © (2025), (Universidad Nacional Autonoma de Mexico). All rights reserved.